2022
DOI: 10.3390/v14050846
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous Codon Usage Analysis of Three Narcissus Potyviruses

Abstract: Narcissus degeneration virus (NDV), narcissus late season yellows virus (NLSYV) and narcissus yellow stripe virus (NYSV), which belong to the genus Potyvirus of the family Potyviridae, cause significant losses in the ornamental value and quality of narcissus. Several previous studies have explored the genetic diversity and evolution rate of narcissus viruses, but the analysis of the synonymous codons of the narcissus viruses is still unclear. Herein, the coat protein (CP) of three viruses is used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Codon usage patterns of viruses reflect evolutionary changes, such as adaption, evolution, evasion from host immune systems, and survival [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Now, only limited reports show the codon usage patterns of plant viruses, such as citrus tristeza virus (CTV) [ 50 ], rice strape virus (RSV) [ 51 ], papaya ringspot virus (PRSV) [ 52 ], potato virus M (PVM) [ 53 ], sugarcane mosaic virus (SCMV) [ 54 ], broad bean wilt virus 2 (BBWV2) [ 55 ], rice black-streaked dwarf virus (RBSDV) [ 56 ], narcissus degeneration virus (NDV) [ 57 ], narcissus late season yellows virus (NLSYV) [ 57 ], and narcissus yellow stripe virus (NYSV) [ 57 ]. Here, the composition and codon usage patterns of TuMV based on the complete genome were estimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Codon usage patterns of viruses reflect evolutionary changes, such as adaption, evolution, evasion from host immune systems, and survival [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Now, only limited reports show the codon usage patterns of plant viruses, such as citrus tristeza virus (CTV) [ 50 ], rice strape virus (RSV) [ 51 ], papaya ringspot virus (PRSV) [ 52 ], potato virus M (PVM) [ 53 ], sugarcane mosaic virus (SCMV) [ 54 ], broad bean wilt virus 2 (BBWV2) [ 55 ], rice black-streaked dwarf virus (RBSDV) [ 56 ], narcissus degeneration virus (NDV) [ 57 ], narcissus late season yellows virus (NLSYV) [ 57 ], and narcissus yellow stripe virus (NYSV) [ 57 ]. Here, the composition and codon usage patterns of TuMV based on the complete genome were estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Low codon usage biases were also observed for RSV, CTV, PRSV, PVM, SCMV, BBWV2, RBSDV, NDV, NLSYV, and NYSV [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. For TuMV, similar lower codon usage patterns were also found with ENC values higher than 35, which indicated a low degree of preference.…”
Section: Discussionmentioning
confidence: 99%
“…Narcissus yellow stripe virus (NYSV) and Narcissus degeneration virus (NDV) CP genes, a recurring preference for A/U in the third codon position across narcissus viruses was observed (He et al, 2022). This comparative analysis sheds light on the shared characteristics and distinctive features of codon usage among different viruses, providing valuable insights into the evolutionary mechanisms and selective pressures governing codon bias in viral genomes.…”
Section: Comparing Our Ndings With Those Of He Et Al (2022) Who Inves...mentioning
confidence: 86%
“…Previous studies on plant virus codons such as sugarcane mosaic virus (SCMV) [ 61 ], papaya ringspot virus (PRSV) [ 62 ], potato virus M (PVM) [ 63 ], citrus tristeza virus (CTV) [ 64 ], broad bean wilt virus 2 (BBWV2) [ 65 ], rice stripe virus (RSV) [ 66 ], rice black-streaked dwarf virus (RBSDV) [ 67 ], yellows virus (NLSYV) (NDV) [ 68 ], narcissus degeneration virus narcissus late season [ 68 ] and narcissus yellow stripe virus (NYSV) [ 68 ] have shown that the codon preference of the virus is weak, which is consistent with our analysis results. This phenomenon may be connected to the effective replication of the virus.…”
Section: Discussionmentioning
confidence: 99%